Mechanical and Formability Evaluation of ST14 Alloys Welded by Friction Stir Welding - Mahmoud Afshari; Nima Fakhralmobasheri; Mohammad Reza Samadi; Amirhossein Alavi; Hossein Norozi Foroushani (Shock and Vibration)
Friction stir welding as one of the modern methods of solid-state welding of steel sheets and aluminum is a highly regarded industry. In these studies, the experimental design and response surface methodology were used. Optimization of experimental conditions and results which are compared with good agreement between the results was observed. The mechanical properties and ductility of welded plates under optimal conditions were studied. Microhardness testing, metallography, tensile testing, and limiting dome height were used to investigate the mechanical properties and formability limit diagram attached, respectively. The results showed that the heat-affected zone is very small and narrow and not easily distinguished from the base metal. In all tests, the failure of the dome height limit in the area was chaos. In all samples welded with the optimal parameters, tensile failure occurred in the base metal region. Turbulence in the region confirms the presence of WC particles. Experimental design and response surface methodology could introduce an optimal state, and the creation of common defects in the FSW process can prevent the binding strength of the guarantee. But due to the lack of proper stirring in the perturbation area in the samples welded with non-optimized parameters, the strength of the connection is not suitable, and samples were broken from the SZ region.